The impact of antegrade intramedullary nailing start site using the SIGN nail in proximal femoral fractures: A prospective cohort study. Issue 2 (February 2018) - Mustafa Diab, Mohamed; Wu, Hao-Hua; Eliezer, Edmund; Haonga, Billy; Morshed, Saam; Shearer, David W.
Abstract: Introduction: In many low and middle-income countries (LMICs) SIGN nail is commonly used for antegrade femoral intramedullary (IM) nailing, using a start site either at the tip of the greater trochanter or piriformis fossa. While a correct start site is considered an essential technical step; few studies have evaluated the impact of using an erroneous start site. This is particularly relevant in settings with limited access to fluoroscopy to aid in creating a nail entry point. The purpose of this study was to evaluate the impact of antegrade SIGN IM nailing start site on radiographic alignment and health-related quality of life. Methods: In this prospective cohort study, adult patients with proximal femur fractures (OTA 32, subtrochanteric zone) treated with antegrade IM SIGN nail at Muhimbili Orthopaedic Institute (MOI), Dar es Salaam, Tanzania were enrolled. Start site was determined on the immediate postoperative X-ray and was graded on a continuous scale based on distance of the IM nail center from the greater trochanteric tip. The primary outcome measurement was coronal alignment on the post-operative x-ray. The secondary outcomes were reoperation rates, RUST scores and EQ5D scores at one year follow-up. Results: Seventy-nine patients were enrolled. 50 of them (63.3%) had complete data at 1 year and were included in the final data analysis. Of the fifty patients, nine (18%) had IM nails placed laterally, 26 (52%) medially and 15 (30%) directly over the tip of the greater trochanter. Compared to a start site at the tip or medial to the greater trochanter, a lateral start site was 9 times more likely to result in a varus malalignment (95% CI: 1.42–57.70, p = 0.021). Conclusions: Lateral start site was associated with varus malalignment. Although lateral start site was not significantly associated with reoperation, varus deformity was associated with higher reoperation rates. Surgeons should consider avoiding a start site lateral to the tip of the greater trochanter or allow the nail to rotate to avoid malalignment when using the SIGN nail for proximal femur fractures.